2018
DOI: 10.1007/s11104-018-3796-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure and functions differ between native and novel (exotic-dominated) grassland ecosystems in an 8-year experiment

Abstract: Aims Grasslands dominated by non-native (exotic) species have replaced purely native-dominated areas in many parts of the world forming 'novel' ecosystems. Altered precipitation patterns are predicted to exacerbate this trend. It is still poorly understood how soil microbial communities and their functions differ between high diversity native-and low diversity exotic-dominated sites and how altered precipitation will impact this difference. Methods We sampled 64 experimental grassland plots in central Texas wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 60 publications
2
11
1
Order By: Relevance
“…As we found previously (Checinska‐Sielaff et al. ), fungal communities were more strongly impacted by the plant community treatment than bacterial communities, demonstrating that novel grassland ecosystems have altered soil fungal communities compared with the native grasslands that they replaced. Although irrigation did not alter the composition of detected microbes (active, dormant, relic), the interactions among community members responded to irrigation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As we found previously (Checinska‐Sielaff et al. ), fungal communities were more strongly impacted by the plant community treatment than bacterial communities, demonstrating that novel grassland ecosystems have altered soil fungal communities compared with the native grasslands that they replaced. Although irrigation did not alter the composition of detected microbes (active, dormant, relic), the interactions among community members responded to irrigation.…”
Section: Discussionsupporting
confidence: 78%
“…Native and exotic communities differed in fungal community composition in the upper soil layer (up to 10 cm) over eight years in a previous study at this site (Checinska‐Sielaff et al. ). However, this is the first study to show that conversion from native to exotic plant species has impacts well beyond the surface soil.…”
Section: Discussionmentioning
confidence: 78%
“…In terms of bacterial and fungal community composition, our samples tended to cluster along a plant species richness gradient from monocultures to 60 species‐mixtures (Figure 1), indicating that plant diversity led to ‘directed’ microbial species turnover, as has been found in previous biodiversity experiments (Grüter et al., 2006; LeBlanc et al., 2015; Schlatter et al., 2015). However, another study with bulk soil from a grassland ecosystem in Texas found that fungal community composition was not influenced by plant diversity but rather by the addition of a single exotic plant species (Checinska Sielaff et al., 2018). Overall, these studies suggest bulk soil microbial communities are less strongly influenced by plant species richness than rhizosphere microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…1), indicating that plant diversity led to “directed” microbial species turnover, as has been found in previous biodiversity experiments (Grüter et al, 2006; LeBlanc et al, 2015; Schlatter et al, 2015). However, another study with bulk soil from a grassland ecosystem in Texas found that fungal community composition was not influenced by plant diversity but rather by the addition of a single exotic plant species (Checinska Sielaff et al, 2018). Overall, these studies suggest bulk soil microbial communities are less strongly influenced by plant species richness than rhizosphere microbial communities.…”
Section: Discussionmentioning
confidence: 99%